2016
DOI: 10.1111/ecin.12363
|View full text |Cite
|
Sign up to set email alerts
|

Regional and Sectoral Evidence of the Macroeconomic Effects of Labor Reallocation: A Panel Data Analysis

Abstract: This article revisits the sectoral shifts hypothesis by examining unemployment fluctuations for 48 U.S. states over the period 1990:M01-2011:M12. We develop a panel approach that incorporates dynamics, parameter heterogeneity, aggregate factors, and cross-sectional dependence (CSD). Our findings provide support for a positive and significant effect of the employment dispersion index on unemployment. This outcome is robust under alternative specifications and measures of employment dispersion. The empirical evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 75 publications
(190 reference statements)
7
14
0
Order By: Relevance
“…unemployment when both heterogeneity and interdependence among EU states are taken into account (albeit lower to the homogenous case). Furthermore, we observe that these heterogeneous estimates (Table 4) 12 Following the theoretical argument of Sarafidis and Wansbeek (2012) and analogously to the findings in Bakas et al (2016), we observe that neglecting to account for cross sectional dependence in the estimation will lead to an upward bias in the estimates. 13 Similarly, the elasticity of unemployment with respect to sigma (based on the CCEMG estimator) will be equal to 6.16% at the sample maximum value of the reallocation index ( = 0.07) (see Table 2).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…unemployment when both heterogeneity and interdependence among EU states are taken into account (albeit lower to the homogenous case). Furthermore, we observe that these heterogeneous estimates (Table 4) 12 Following the theoretical argument of Sarafidis and Wansbeek (2012) and analogously to the findings in Bakas et al (2016), we observe that neglecting to account for cross sectional dependence in the estimation will lead to an upward bias in the estimates. 13 Similarly, the elasticity of unemployment with respect to sigma (based on the CCEMG estimator) will be equal to 6.16% at the sample maximum value of the reallocation index ( = 0.07) (see Table 2).…”
Section: Resultssupporting
confidence: 75%
“…16 As in Bakas et al (2016), the impact of the dispersion index depends on the level of its disaggregation. The extent of sectoral decomposition determines the magnitude of labor restructuring that is captured.…”
Section: Resultsmentioning
confidence: 99%
“…Samson (1985) tested the importance of sectoral changes in explaining short‐run fluctuations in unemployment and included that much of the variability in short‐run unemployment is the consequence of large sectoral flows of employment. Other studies carried out by Bakas et al (2017), Garonna and Sica (2000), and Zeren (2020) have shown similar results.…”
Section: Literature Reviewsupporting
confidence: 72%
“…Still, Samson (1985) and Charette and Kaufmann (1987) found that this correction did not greatly affect their results, while Abraham and Katz (1986) and Neelin (1987) reported that the new dispersion measures lose their statistical power. Similarly, Bakas et al (2017) showed that the standard and the "purged" Lilien index exhibits a similar impact on unemployment. Loungani et al (1990) proposed a different measure of sectoral shocks to address the problem raised by Abraham and Katz (1986).…”
Section: The Impact Of Job Reallocation On Unemployment: a Review Of ...mentioning
confidence: 87%
See 1 more Smart Citation